2013
DOI: 10.1002/jgra.50489
|View full text |Cite
|
Sign up to set email alerts
|

The VLF fingerprint of elves: Step‐like and long‐recovery early VLF perturbations caused by powerful ±CG lightning EM pulses

Abstract: [1] Subionospheric VLF recordings are investigated in relation with intense cloud-to-ground (CG) lightning data. Lightning impacts the lower ionosphere via heating and ionization changes which produce VLF signal perturbations known as early VLF events. Typically, early events recover in about 100 s, but a small subclass does not recover for many minutes, known as long-recovery early events (LORE). In this study, we identify LORE as a distinct category of early VLF events, whose signature may occur either on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 43 publications
9
58
5
Order By: Relevance
“…Anyway our example endorses the observation of Salut et al (2012) that long recovery events are attributed predominantly to lightning discharges occurring over the sea. So with regard to long recovery events it is especially promising to analyze propagation paths crossing regions with frequent and strong thunderstorm activity over the sea, for example the Mediterraneans during winter time, see Haldoupis et al (2013), or the Indian ocean, as reported by Salut et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyway our example endorses the observation of Salut et al (2012) that long recovery events are attributed predominantly to lightning discharges occurring over the sea. So with regard to long recovery events it is especially promising to analyze propagation paths crossing regions with frequent and strong thunderstorm activity over the sea, for example the Mediterraneans during winter time, see Haldoupis et al (2013), or the Indian ocean, as reported by Salut et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Early VLF perturbations associated with elves have been detected successfully on several occasions, Inan et al ( , 2010; Mika et al (2006). It is proposed, that LORES are caused by large and long-lived electron density enhancements in the upper D-region ionosphere caused by intense positive or negative cloud to ground (CG+/−) lightning discharges, Haldoupis et al (2012Haldoupis et al ( , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The association of LOREs with both positive and negative polarity flashes, in addition to the observations of large elves and elve‐sprite pairs in association with LOREs reported by Haldoupis et al [], led Haldoupis et al [] to conclude that LOREs were produced by ionospheric conductivity changes associated with elves, due to the polarity‐invariant theory of elve production by the lightning electromagnetic pulse [e.g., Barrington‐Leigh and Inan , ; Newsome and Inan , ]. Their argument, however, disregards evidence that −CGs account for nearly half, if not more, of all sprite halos [e.g., Newsome and Inan , ; Williams et al , ] and that rare circumstances of “negative” sprites have been observed [e.g., Barrington‐Leigh et al , ; Taylor et al , ; Li et al , ].…”
Section: Introductionmentioning
confidence: 98%
“…Recent statistical studies of LOREs have identified a number of important lightning discharge properties that are associated with LOREs. Haldoupis et al [] and Salut et al [] report that both the probability of detecting an early VLF event and the expected event recovery duration increase with lightning peak current inferred from lightning locating systems. A large number of LOREs have been associated with lightning flashes occurring over oceans [e.g., Cotts and Inan , ; Salut et al , ], which may in part be due to the higher occurrence of oceanic, negative flashes with large inferred peak currents [ Said et al , ] and large inferred charge moment changes [ Füllekrug et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation